THE EDUCATION OF AKHLAK IN THE ALGHAZALY AND IBNU MASKAWAIH'S PERSPECTIVE (Comparative Study of Educational Thought in Kitab Ihya”Ulumuddin Dan Kitab Tahdzib Al-Akhlaq Wa Tathir Al-A’raq) - Husenudin Ahmadi; Nana Jumhana; Erdi Rujikartawi (AT-TURATS, 2020)
This qualitative research was conducted by the writer with a background on the importance of moral behavior (noble character) for humanity through the figure of the Prophet Muhammad. who has great morals (khulukun adzim). The formulation of the problem in this study is "How is the concept of moral education according to the perspective of Al-Ghazaly in the book of Ihya'Ulumuddin, How is the concept of moral education according to the perspective of Ibnu Maskawaih in the book Tahdzib Al-Akhlak, How is the comparative analysis between the concept of Al-Ghazaly and Ibnu Maskawaih about education morals and reflection of similarities and differences in the concepts of both. The method used by researchers in research related to this thesis material is descriptive method through a qualitative approach.The results of this author's research are that both of them agree on the meaning and nature of moral education, regarding the aims and benefits of moral education, there are two classifications of morals namely good morals and bad morals, there are two methods of moral education according to Al-Ghazaly namely the al-mujahadah method and arriyadlah and according to Maskawaih namely the method of takrir al-mawaidz, al-'ilaj, arriyadlah, criteria and scope of good moral education material and bad moral material, regarding the main morals of moral education there are four namely Al-hikmah, al- ' iffah, ash-shay'ah and al-'adlu or al-'are.